DAMPAK SERTIFIKAT HALAL DAN BIAYA TERHADAP KEPUASAN KONSUMEN - Harahap, Sunarji; Rahmatsyah, Rahmatsyah; Kusdino, Prayogi (Jaksya: Jurnal Akuntansi Syariah, 2024)
Customers of KFC Simpang Lima Fast Food Restaurant in Banda Aceh are the subjects of this study. This study aims to provide the impact of halal certification and in accordance with restaurant customer satisfaction. Primary data were collected through distributing questionnaires to KFC fast food restaurant customers as an example, while secondary data from previous studies and journals. This is a factor that has a partial effect of halal certification. significant on the level of consumer satisfaction who consume Kentucky Fried Chicken, which is intended because Tcount is greater than Ttable (4.927 is greater than 1.66071), which means that the Halal Certification variable has a partial positive and significant effect on customer happiness. Partially, the Price variable has a significant effect on consumer satisfaction who consume KFC which is determined by Tcount Ttable (4.123 1.66071) meaning that the Price variable has a partial positive and significant effect on Customer Satisfaction. Simultaneously, the Halal Certificate and Price variables have a significant influence. From the test results, F countF table (47.5183.09). This means that the Halal Certificate (X1) and Price (X2) variables work together and will influence Customer Satisfaction.